Control Systems in Engineering and Optimization Techniques - Balasubramaniam, P.; Thambiayya, Sathiyaraj; Ratnavelu, Kuru; Wang, JinRong (IntechOpen, 2022)
The portfolio diversification strategy study is useful to help investors to plan for the best investment strategy in maximizing return with the given level of risk or minimizing risk. Further, a new set of generalized sufficient conditions for the existence and uniqueness of the solution and finite-time stability has been achieved by using Generalized Gronwall-Bellman inequality. Moreover, a novel development is proposed to solve classical control theory's difference diagrams and transfer functions. Advanced TCP strategies and free parametrization for continuous-time LTI systems and quality of operation of control systems are presented.